Фауна пухоедов птиц отряда чайкообразных Северного Причерноморья - Федоренко, И.А. (Вестник зоологии, 1969)
Studying 13 species of birds from the Lariformes order, that were found in the North Black Sea area, the author detected in them 18 species of Mallophaga which are the specific parasites of Lariformes.
An extensiveness of infection accounts for 95.6%, the average intensity of infection being 15 individuals. The following four species of Mallophaga are observed for the first time in the USSR fauna: Austromenopon fuscofasciatum, Quadraceps anagrapsus, Qu. normifer stellaepolaris and Saemundssonia euryrhyncha.